Value Chain Analysis of Milled Rice Produce in Husking Rice Mill (Bangladesh Rice Journal, 2023)
This study was aimed to identify the present status of rice milling, map and analyze milled rice along with associated constraints and recommend priority areas of interventions using primary and secondary sources data during the period of 2012-14. In a quantitative survey, stratified random sampling was used to identify respondents, while qualitative investigations involved focus groups and key informant interviews. In the country, there are about 15,500 husking mills, 650 semi-automatic mills, and 300 automatic rice mills. Husking mills still dominate the rice milling sector and it covers about 70% of total milled rice production. However, recent trends show that the husking rice mills fail to compete with modern automatic and semi-automatic rice mills in terms of quality finished products and market demand, in turn shifting to semi-automatic and automatic rice mills is going on. The milling capacity and capacity utilization of husking mills was found to be 0.8-1.0 th-1 and 34%, respectively. Milling cost, profit per ton of fine parboiled rice and BCR for husking were found to be Tk. 2601, Tk. 3637 and 1.4, respectively. The profit margin for parboiled fine rice processed in a husking mill was found to be 37.04%. Employment opportunities in terms of labor and staff requirement for husking mills were found to be 14.17 man hours per metric ton of paddy and 6.95 man hours per tonne of paddy, respectively. Husking rice mills produce more broken, less head rice recovery and quality is less than automatic rice mills. Beside these, in husking mill bran and husk are mixed together that’s not suitable for edible oil extraction and briquette production. In terms of quality of rice e.g. less broken rice, absence of stones and black kernels, brightness, color etc., the rice mills having modern equipment produce higher quality rice, with higher market demand and higher profit making ability compared to rice mills having traditional equipment.Bangladesh Rice J. 26 (2): 19-39, 2022